The methodological foundations of social and cultural constructing - М N Filatova (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2009)
Social projecting has been gaining in a particular importance in the contemporary society since it is with it that the innovative activity in all the domains of society's vital functions is associated. Social projecting in education system is a form of social and cultural projecting, the main stages and distinctive features of which are analyzed in this very item.